Mesoporous TiO2/TiC@C Composite Membranes with Stable TiO2-C Interface for Robust Lithium Storage - Zhang, Wei; Zu, Lianhai; Kong, Biao; Chen, Bingjie; He, Haili; Lan, Kun; Liu, Yang; Yang, Jinhu; Zhao, Dongyuan (iScience, 2018)
Transition metal oxides/carbon (TMOs/C) composites are important for high-performance lithium-ion batteries (LIBs), but the development of interface-stable TMOs/C composite anodes for robust lithium storage is still a challenge. Herein, mesoporous TiO2/TiC@C composite membranes were synthesized by an in situ carbothermic reduction method. TiC nanodots with high conductivity and electrochemical inactivity at the TiO2-C interface can significantly enhance the electrical conductivity and structural stability of the membranes. Finite element simulations demonstrate that the TiO2/TiC@C membranes can effectively alleviate tensile and compression stress effects upon lithiation, which is beneficial for robust lithium storage. When used as additives and binder-free electrodes, the TiO2/TiC@C membranes show excellent cycling capability and rate performance. Moreover, a flexible full battery can be assembled by employing the TiO2/TiC@C membranes and shows good performance, highlighting the potential of these membranes in flexible electronics. This work opens an avenue to constructing interface-stable composite structures for the next-generation high-performance LIBs. [Display omitted] •Mesoporous TiO2/TiC@C membranes were synthesized by a simple method•This method can be extended to the synthesis of other metal oxide/metal carbide@C•The TiC nanodots can alleviate tensile and compression stress effect upon lithiation•Long working life and excellent rate performance can be achieved Composite Materials; Nanomaterials; Energy Materials